Nailfold Capillaroscopy in Systemic Sclerosis Patients with and without Pulmonary Arterial Hypertension: A Systematic Review and Meta-Analysis - Minopoulou, Ioanna (J Clin Med, 2021)
Systemic sclerosis (SSc)-related pulmonary arterial hypertension (SSc-PAH) is a leading cause of mortality in SSc. The extent of peripheral microvasculopathy assessed through nailfold capillaroscopy might correlate with the presence of PAH in SSc patients. We searched the PubMed, Cochrane Library, Scopus, and Web of Science databases and performed a random effects meta-analysis of observational studies comparing nailfold capillaroscopic alterations in SSc-PAH versus SSc-noPAH patients. Weighted mean differences (WMD) with the corresponding confidence intervals (CIs) were estimated. The quality of the included studies was evaluated using a modified Newcastle–Ottawa scale. Seven studies with 101 SSc-PAH and 277 SSc-noPAH participants were included. Capillary density was marginally reduced in the SSc-PAH group (WMD: −1.0, 95% CI: −2.0 to 0.0, I(2) = 86%). This effect was strengthened once PAH diagnosis was confirmed by right heart catheterization (WMD: −1.2, 95% CI: −2.3 to −0.1, I(2) = 85%). An increase in capillary loop width was observed in SSc-PAH compared to SSc-noPAH patients (WMD: 10.9, 95% CI: 2.5 to 19.4, I(2) = 78%). Furthermore, SSc-PAH patients had a 7.3 times higher likelihood of active or late scleroderma pattern (95% CI: 3.0 to 18.0, I(2) = 4%). SSc-PAH patients presented with worse nailfold capillaroscopic findings compared to SSc-noPAH patients.